Implementation of Google Classroom and Audiovisual Media Utilization in Sixth Grade Indonesian Language Online Learning - Salma Fithrotun Nisa'; Aninditya Nugraheni (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
With the existence of several obstacles to the online learning process, it is necessary to have the right media to reduce learning problems. This research was conducted to find an overview of the online learning implementation by utilizing the Google Classroom application with audio-visual media in Indonesian subjects during the COVID-19 pandemic. In this research, the method applied a qualitative approach, with a descriptive research type. The results of this study revealed that some Indonesian teachers in sixth grade of SD/MI (Elementary schools) agreed that the use of the Google Classroom application with audio-visual media was an alternative effort to facilitate them and their students during online learning activities. The Google Classroom application provided services, such as assignment, grading, material, and much more. These services showed that the application was very suitable to be applied during online learning in this study. As a form of creativity for Indonesian language teachers in delivering learning materials, audio-visual media were chosen to create a learning atmosphere to be exciting, fun, and not boring even though not face to face. Besides, the audio-visual media application is expected to make it easier for students to absorb the material being taught. Thus, parents, teachers, and the government's roles are vital in students’ learning achievement and enthusiasm during online learning